Implementasi Arsitektur dan Desain Interior “The Story Of Laun” - Fithria Ariesta Cambodia; Gervasius Herry Purwoko; Rani Prihatmanti (Universitas Ciputra Surabaya, 2016)
In the globalization era, people from middle low to middle high social strata become increasingly aware of the importance of interior consultants. This phenomenon is quite ubiquitous not only in nearly all-urban areas throughout Indonesia but also in rural areas: they are fully aware of having comfortable buildings. In fact, high price of the buildings still become one of big problems for middle low families. Located near Surabaya, Gresik has a favorable chance to be one of the most developing cities. Many of Gresik citizens, however, are still living below poverty level. People of Betoyo village are intended to build an At-Thoyibah orphanage for children so that they could have a better living standard. FIARCA Interior Consultant who is concerned with social issues attempts to offer solution by giving education about architecture design and building interior. Pleasant Islamic interior concept has been intentionally chosen in order to increase the children’s learning interests.